Clinical Relevance of Elevated Serum Carcinoembryonic Antigen in Allergic Bronchopulmonary Aspergillosis/Mycosis: A Multicenter Retrospective Study - Ge H; Cai R; Chen X; Liu B; Hu X; Deng S; Li H; Dai L; Tang J; Tang H; Gong X; Wu C; et al. (Journal of Asthma and Allergy)
Huan Ge,1,2,* Runjin Cai,1,2,* Xuemei Chen,1,2 Bin Liu,3 Xinyue Hu,1,2 Shuanglinzi Deng,1,2 Hui Li,4 Lixue Dai,5 Jiale Tang,1,2 Huan Tang,1,2 Xiaoxiao Gong,1,2 Chendong Wu,1,2 Guo Wang,1,2 Guotao Li,6,* Bing Liu,3,7,* Jun Wang,5,* Yuling Tang,4 Xiaozhao Li,2,8 Juntao Feng1,2 1Department of Respiratory Medicine, National Key Clinical Specialty, Branch of National Clinical Research Center for Respiratory Disease, Xiangya Hospital, Central South University, Changsha, People’s Republic of China; 2National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Central South University, Changsha, People’s Republic of China; 3Department of Pulmonary and Critical Care Medicine, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 4Department of Respiratory Medicine, The First Hospital of Changsha, Changsha, People’s Republic of China; 5The Second Department of Respiratory Disease, Jiangxi Provincial People’s Hospital, The First Affiliated Hospital of Nanchang Medical College, Nanchang, People’s Republic of China; 6Department of Infectious Diseases, Luoyang Central Hospital Affiliated to Zhengzhou University, Luoyang, People’s Republic of China; 7Wuhan Research Center for Infectious Diseases and Cancer, Chinese Academy of Medical Sciences, Wuhan, People’s Republic of China; 8Department of Nephrology, Xiangya Hospital, Central South University, Changsha, People’s Republic of China*These authors contributed equally to this workCorrespondence: Juntao Feng, Department of Respiratory Medicine, Xiangya Hospital, Central South University, No. 87 Xiangya Road, Kaifu District, Changsha, Hunan, 410008, People’s Republic of China, Email jtfeng1976@csu.edu.cn Yuling Tang, Department of Respiratory Medicine, The First Hospital of Changsha, No. 311 Yingpan Road, Kaifu District, Changsha, Hunan, 410005, People’s Republic of China, Email tyl71523@sina.comBackground: Allergic bronchopulmonary aspergillosis/mycosis (ABPA/M) is a complex non-infectious pulmonary benign disease characterized by an immune response against aspergillus/fungus. Carcinoembryonic antigen (CEA), typically recognized as a tumor marker, also elevated in certain benign diseases. Few studies on ABPA/M cases presenting with elevated serum CEA levels have been reported.Patients and Methods: A cohort of 115 patients diagnosed as ABPA/M were divided into two groups (CEA normal and CEA elevated). The characteristics of ABPA/M patients in terms of its demographic profile, clinical symptoms, pertinent clinical laboratory examinations were analyzed. Levels of cytokines (IL-4, IL-5, GM-CSF, IFN-γ) were analyzed by enzyme-linked immunosorbent assay. Comparative evaluation included pre-therapy and post-treatment eosinophil count and total IgE level, to evaluate therapeutic disparities between the two groups.Results: Among 115 cases of ABPA/M, 32 exhibited elevated serum CEA levels above baseline and 83 were normal. ABPA/M patients with elevated serum CEA tended to be younger (50, IQR [43– 56] years vs 59, IQR [47– 68] years; P < 0.05) with superior pulmonary function (FEV1/FVC ratio, 65.1% (44.2, 79.6) vs 79.1% (65.2, 84.2), P < 0.05), and showed marginally higher baseline levels of the total IgE (P < 0.05), blood eosinophils counts and ratios (P < 0.01) compared to those with normal CEA. Higher serum levels of IL-4, IL-5, GM-CSF and IFN-γ in ABPA/M patients with elevated serum CEA levels were observed (P < 0.0001). After treatment (at 12w), compared to ABPA/M patients with normal serum CEA, the decrease in eosinophil count and total IgE levels was less pronounced in ABPA/M patients with elevated serum CEA eosinophil count, 523± 481.66 vs 267± 200.68, P < 0.05; total IgE, 619± 680.47 vs 263± 400.90, P < 0.05), which indicates a poor response to treatment.Conclusion: Monitoring serum CEA levels may serve as a supplementary tool in the clinical management of ABPA/M patients.Keywords: allergic bronchopulmonary aspergillosis/mycosis, carcinoembryonic antigen, IgE, eosinophils